Comparison of Metformin and Insulin in the Treatment of Gestational Diabetes - Faris Mohammedamin Qari,; Maaz Ahmed Raei,; Nahd Hasan M Alesawy,; Abdullah Mohammed Al Yamani,; Sultan Obaid Abed Almalki,; Marwan Faisal Ismail,; Azizah Ibrahim Al Wagdany,; Kawther Hassan Aleisawi,; Fahad Hassan Aleisawi,; Atallah Mater Alamri,; Mofareh Bakheet Alzahrani,; Ali Yahya Alzahrani,; et al. (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: Gestational diabetes mellitus (GDM) is a prevalent complication of gestation, impacting up to sixteen percent of all pregnancies, contingent upon the criteria for diagnosis. Aim: To evaluate the efficacy of metformin versus insulin in managing GDM. Patients and methods: A comprehensive literature review has been performed in the following databases: PubMed, EMBASE, Cochrane Library, and Google Scholar. The search technique encompassed the terms: "gestational diabetes," "metformin," "insulin," "treatment," "randomized controlled trial," and "outcome." The search has been confined to papers published between January 2008 and December 2023. Results: Nine studies reported (NICU admissions) and all can be used. A significant heterogeneity has been identified. Therefore, a random-effect model has been utilized for analysis (I² = 49%, P-value equal 0.05). The combined mean difference and ninety five percent confidence intervals were 0.72 (0.56 to 0.93). The combined result exhibits a highly statistically significant distinction among groups regarding (NICU admissions) (Z = 2.53, P-value equal 0.01). Seven studies reported (Neonatal hyperbilirubinemia) and all can be used. Insignificant heterogeneity has been detected. Therefore, a random-effect model was used for analysis (I² = 0%, P=0.53). The combined mean difference and ninety five percent confidence intervals were 0.96 (0.65 to 1.42). The combined result demonstrates no statistically significant variance among groups regarding (Neonatal hyperbilirubinemia) (Z-value equal 0.19, P-value equal 0.85). Conclusion: Metformin offers short-term benefits in treating gestational diabetes mellitus (GD), but long-term studies are needed to evaluate its safety and effectiveness.